2018
DOI: 10.25077/amar.2.2.59-81.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Micro and Macroeconomic on Investment Opportunity

Abstract: The purpose of this study is to obtain results: the influence of micro and macroeconomic factors of the company on investment opportunities. This research is conducted in five ASEAN countries, such as; Indonesia, Malaysia, Singapore, Thailand, and the Philippines (ASEAN-5). The microeconomic factors are measured by firm size, financial risk, profitability, and debt policy. The macroeconomic factors are measured by interest rates, exchange rates, inflation, and economic growth. The analysis unit of this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A high inflation rate will increase interest rates which in turn will reduce investment. As mentioned above, Lakonishok et al (1994) and Adiputra & Affandi (2018) states that lower economic growth, as indicated by higher inflation, results in a lower IOS (i.e. price against book value).…”
Section: Inflation and Investment Opportunity Setmentioning
confidence: 94%
See 3 more Smart Citations
“…A high inflation rate will increase interest rates which in turn will reduce investment. As mentioned above, Lakonishok et al (1994) and Adiputra & Affandi (2018) states that lower economic growth, as indicated by higher inflation, results in a lower IOS (i.e. price against book value).…”
Section: Inflation and Investment Opportunity Setmentioning
confidence: 94%
“…However, on the other hand, the use of large debt and supported by good utilization will provide a positive value for the company's future growth. Research conducted by Adiputra & Affandi (2018) found that the solvency that is measured by debt-to-equity ratio has a positive influence with the investment opportunities set. SMEs are trying to increase the scale of their companies to be bigger than before by relying on debt.…”
Section: Leverage and Investment Opportunity Setmentioning
confidence: 99%
See 2 more Smart Citations